2013
DOI: 10.1103/physreve.87.052402
|View full text |Cite
|
Sign up to set email alerts
|

Phase-dependent premelting of self-assembled phosphonic acid multilayers

Abstract: Melting and premelting phenomena in self-organized organic systems have been extensively explored in the literature, exploring distinct behaviors of different molecule lengths and morphologies. Nevertheless, the influence of the supramolecular assembly configuration on the occurrence of premelting remains poorly explored. Here we use phosphonic acids as model systems for self-organized molecular assemblies. These molecules exhibit long-range order on different types of substrates. The balance between chain-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The simulations were carried out for coherent lamellar domains of 7 stacked bilayers (14 molecules), with a relative volume of 1:2 for bilayers with heights of 3.85 and 3.68 nm, respectively. Such a relatively reduced amount of stacked bilayers, if compared to results on phosphonic acids with other alkyl chain lengths, , is responsible for the observed broad peaks, indicating a degree of structural flexibility of TPA multilayers, which will be further explored here.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The simulations were carried out for coherent lamellar domains of 7 stacked bilayers (14 molecules), with a relative volume of 1:2 for bilayers with heights of 3.85 and 3.68 nm, respectively. Such a relatively reduced amount of stacked bilayers, if compared to results on phosphonic acids with other alkyl chain lengths, , is responsible for the observed broad peaks, indicating a degree of structural flexibility of TPA multilayers, which will be further explored here.…”
Section: Resultsmentioning
confidence: 94%
“…One clearly observes 3.7 nm height steps (the lower step is a multiple of this value, with a 7.3 nm height), which are equivalent to stacked bilayers, as also observed in similar molecules with alkyl chains containing 18 and 8 carbon atoms. 18,21,29 The profile extracted from the DdPA AFM images, shown in Figure 2b, suggests an amorphous or poorly organized molecular clustering. Among all DdPA samples, no steplike or terracelike feature was retrieved by AFM analysis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, we excluded the formation of supramolecular assemblies of the alkyl phosphonic acids alone [57] by collecting XRD patterns of TDPA in either TOA or octadecene (ODE) at different temperatures ( Figure S11). As the resulting patterns did not match with the lamellar peaks, we concluded that Cu must be involved in the structure, and that the lamellae must be a coordination polymer.…”
Section: Identifying the Composition Of The Intermediate Lamellar Strmentioning
confidence: 99%
“…We know from previous studies that OPA bilayers remain ordered up to ∼100 °C. 22,34 From room temperature up to approximately 75 °C, three lamellar configurations coexist, each one with a particular tilt with respect to the surface-normal direction. These configurations were thoroughly studied in ref 22 and are schematically represented in Figure 4a.…”
mentioning
confidence: 99%